(untitled) (Research, Society and Development, 2022)
Oral health condition is an inseparable component of health and is a factor of great interference in the quality of life of individuals. Caries and periodontal disease are the major causes of consequences that have an impact on the quality of life of the individuals. Epidemiological surveys are necessary both for the knowledge of the prevalence of oral diseases as well as to estimate treatment needs. Therefore, the objective of this study was to evaluate the need for dental treatment in children and adults treated at the school clinic of the School of Dentistry of Recife - FOR. We analyzed 244 medical records, the codes and criteria used were: No treatment, restoration of a dental surface, restoration of two or more dental surfaces, aesthetic facet, pulp treatment, extraction, remineralization of white spot, sealant, no information, scraping, upper partial protese, lower partial protese, full protese, crown for any reason, implant, periodontal surgery, dental whitening, fiberglass pin. The patients who sought care in the clinics of the School of Dentistry of Recife - FOR were mostly women and with a mean age of 36 years. The most common treatment performed at the school clinic of the School of Dentistry of Recife - FOR was restoration of a surface. The study demonstrates the need for oral health promotion.